Application of multiple regression analysis to study the relationship between eeg rhythms at persons with mental retardation - B. Lobasyuk; L. Bartsevich; A. Zamkovaya (Kazimierz Wielki University, 2022)
Using the calculation of coefficients of multiple linear regression of two-dimensional correlation, we studied the mutual influences (functional connectivity) between the amplitudes of EEG rhythms in people with mental retardation. Multiple regression equations were geometrically interpreted using polycyclic multigraphs. As a result of the studies and calculations, it was found that in mental retardation, the number of regression coefficients of the two-dimensional correlation is determined to be greater than in the norm. In the sinistrals control group, the coefficients of multiple regression of two-dimensional correlation were determined more than in the dextrals control group. In mentally retarded sinistrals, the number of multiple regression coefficients was determined to be less than in mentally retarded dextrals, but the number of bivariate correlation coefficients was larger. The resulting increase in correlation coefficients may indicate an increase in tone in sinistrals suffering from mental retardation compared to dextrals with mental retardation. The mechanism of this increase in tone is realized by linear functions.